Enhanced solubility and dissolution of ketoconazole through co-amorphization with fumaric and tartaric acids via co-milling - Indra, Indra; Nurani, Rani; Wulandari, Winda Trisna (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the co-amorphization of ketoconazole (KTZ) with fumaric acid (FA) and tartaric acid (TA) through co-milling, aiming to enhance the solubility, stability, and dissolution properties of this poorly water-soluble antifungal. Phase diagrams obtained via Hot Stage Microscopy (HSM) showed eutectic-like behavior at equimolar ratios for both KTZ-FA and KTZ-TA systems, with a more pronounced melting point depression in KTZ-FA, indicative of stronger molecular interactions fostering stable amorphous formation. Solid-state characterization using Powder X-ray Diffraction, Fourier Transform Infrared Spectroscopy, and Differential Scanning Calorimetry confirmed amorphization and showed significant hydrogen bonding in KTZ-FA. Further analyses with Thermogravimetric Analysis and Scanning Electron Microscopy demonstrated reduced thermal stability and particle size, accompanied by homogenous amorphous morphologies. Solubility and dissolution studies highlighted remarkable improvements: solubilities of KTZ-FA and KTZ-TA were 11.652 mg/mL and 8.750 mg/mL, respectively, compared to 0.060 mg/mL for pure KTZ. Dissolution profiles indicated superior performance of KTZ-FA at neutral pH, attributed to enhanced hydrogen bonding. Taken together, these findings position the co-amorphous KTZ–FA and KTZ–TA systems as promising candidates for developing rapid-acting oral antifungal dosage forms with improved bioavailability and patient compliance.